2018
DOI: 10.3390/app8081229
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Response Analysis for a Floating Offshore Wind Turbine Integrated with a Steel Fish Farming Cage

Abstract: A state-of-the-art concept integrating a deepwater floating offshore wind turbine with a steel fish-farming cage (FOWT-SFFC) is presented in this paper. The configurations of this floating structure are given in detail, showing that the multi-megawatt wind turbine sitting on the cage foundation possesses excellent hydrostatic stability. The motion response amplitude operators (RAOs) calculated by the potential-flow program WAMIT demonstrate that the hydrodynamic performance of FOWT-SFFC is much better than OC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…The figures have also shown that the response of the testbed to short circuit satisfies requirements of high speed, selectivity and sensitivity. Dynamic response of the testbed to the short circuits is therefore verified to be valid and consistent with established short circuit theory [18]- [21].…”
Section: Discussion Of Resultssupporting
confidence: 73%
“…The figures have also shown that the response of the testbed to short circuit satisfies requirements of high speed, selectivity and sensitivity. Dynamic response of the testbed to the short circuits is therefore verified to be valid and consistent with established short circuit theory [18]- [21].…”
Section: Discussion Of Resultssupporting
confidence: 73%
“…However, the added damping matrix B from WAMIT only considers the radiation damping resulting from the oscillation of the steel cage in waves. Due to the fact that there are fish nets and a large number of slender members in the substructure of the WSA, the viscous drag damping induced by flow separation [14] is more significant than the radiation damping and must be taken into account for the hydrodynamic analysis. Therefore, an external liner damping matrix, B E , is introduced into WAMIT.…”
Section: Response Amplitude Operators and Natural Periods Of Wsamentioning
confidence: 99%
“…Site metocean conditions, fabrication, towing, and installation are all important factors that determine the foundation type. Although TLP was widely developed in oil and gas industry for many years, it has great challenges in terms of tendon installation, higher marine operation cost, and the change in tendon tension resulting from tidal variations [14]. The semi-submersible foundation is characterized by a large displacement and a large water plane area contributing to good hydrostatic stability.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical results indicated that the motions of the modified spar-type floating offshore wind turbine (FOWT) in all of the modes were smaller than those of the OC3 Hywind FOWT, except in heave mode over 0.3 rad/s. Zheng et al [32] suggested a state-of-the-art concept integrating a deep-water floating offshore wind turbine with a steel fish-farming cage (FOWT-SFFC). Aero-hydro-servo-elastic modeling and time domain simulations were carried out by FAST to examine the dynamic response of FOWT-SFFC for several environmental conditions.…”
Section: Introductionmentioning
confidence: 99%